High thermal durability of a layered Cs4CoII[WV(CN)8]Cl3 framework: crystallographic and 133Cs NMR spectroscopic studies. Issue 48 (8th August 2016) - Nakabayashi, Koji; Chorazy, Szymon; Miyamoto, Yasuto; Fujimoto, Takashi; Yazawa, Koji; Takahashi, Daisuke; Sieklucka, Barbara; Ohkoshi, Shin-ichi
Abstract : High-temperature crystal structures of a thermally durable cyanido-bridged metal assembly revealed by single-crystal X-ray structural analyses and solid-state NMR studies. Abstract : Temperature-variable single-crystal synchrotron X-ray diffraction and 133 Cs NMR studies were performed for a cyanido-bridged layered metamagnet, Cs4 Co II [W V (CN)8 ]Cl3 (1 ), to elucidate the origin of its unusually high thermal durability up to ca. 523 K (250 °C).1 reveals a layered structure composed of negatively charged two-dimensional cyanido-bridged Co–W layers ({Co II [W V (CN)8 ]Cl3 } 4− ) and cesium ions between and within the layers, where there is a lack of both non-coordinated and coordinated solvent molecules that is an important and characteristic feature of the crystal structure. The cesium ions are surrounded by chlorides and cyanides of the coordination layers, and some Cs + ⋯Cl −, Cs + ⋯N, and Cs + ⋯C distances are shorter than the estimated sums of an ionic radius of Cs + and ionic or van der Waals radii of Cl − /CN − . These short distances suggest strong interactions between Cs + and Cl − /CN −, which stabilize the crystal structure by connecting the layers. The temperature-dependent single-crystal structural analyses show that there is no significant structural change upon heating up to 473 K, and indicate that the short distances between Cs + and Cl − /CN − still remain. Thus, the high thermal durability of1 is due to not only the absence of solvent molecules but also the existence of strong Cs + ⋯Cl − and Cs + ⋯ − NC interactions. The 133 Cs NMR spectrum shows four peaks assignable to the four independent Cs + ions in the crystal structure. The observed peaks were located in high ppm owing to the hyperfine interactions between the nuclear spin of Cs and electron spins from the magnetic centers Co II and W V . As temperature increased, the peaks moved to low ppm, and the shifts of the peaks are expressed by the Curie–Weiss law indicating no large structural changes around Cs + ions, that is, the Cs + ions are fixed at the same positions. This proves the presence of strong interactions involving Cs + and terminal ligands of cyanido-bridged layers of1 being responsible for its high thermal stability.